Validating the revised plagiarism attitude scale among Malaysian medical sciences students: a psychometric study in multilingual contexts - Zhenxiao Zhang; Yang Liu; Hamid Sharif-Nia (BMC Medical Education)
Abstract Objective This study aims to validate the revised plagiarism attitude scale among Malaysian medical sciences students, particularly focusing on those for whom English is a second language (L2), to understand their perceptions and attitudes towards plagiarism. Study design A cross-sectional study was conducted involving 549 participants enrolled in medical science programs across Malaysia. Methods The research employed exploratory and confirmatory factor analyses to assess the psychometric properties of the revised plagiarism attitude scale. Key dimensions identified include plagiarism triggers, rationalizing plagiarism, and perceptions of plagiarism severity. Results The scale exhibited high reliability and strong construct validity, with its item structure consistent with previous studies. The findings highlight the significant influence of linguistic and cultural factors on students’ attitudes towards plagiarism. Conclusions This research provides a reliable tool for assessing plagiarism behaviors in multilingual contexts and offers insights for developing targeted educational interventions aimed at enhancing linguistic competence and promoting academic integrity among future healthcare practitioners.